Arctic sea surface height variability and change from satellite radar altimetry and GRACE, 2003–2014. Issue 6 (24th June 2016) - Armitage, Thomas W. K.; Bacon, Sheldon; Ridout, Andy L.; Thomas, Sam F.; Aksenov, Yevgeny; Wingham, Duncan J.
Abstract: Arctic sea surface height (SSH) is poorly observed by radar altimeters due to the poor coverage of the polar oceans provided by conventional altimeter missions and because large areas are perpetually covered by sea ice, requiring specialized data processing. We utilize SSH estimates from both the ice‐covered and ice‐free ocean to present monthly estimates of Arctic Dynamic Ocean Topography (DOT) from radar altimetry south of 81.5°N and combine this with GRACE ocean mass to estimate steric height. Our SSH and steric height estimates show good agreement with tide gauge records and geopotential height derived from Ice‐Tethered Profilers. The large seasonal cycle of Arctic SSH (amplitude ∼5 cm) is dominated by seasonal steric height variation associated with seasonal freshwater fluxes, and peaks in October–November. Overall, the annual mean steric height increased by 2.2 ± 1.4 cm between 2003 and 2012 before falling to circa 2003 levels between 2012 and 2014 due to large reductions on the Siberian shelf seas. The total secular change in SSH between 2003 and 2014 is then dominated by a 2.1 ± 0.7 cm increase in ocean mass. We estimate that by 2010, the Beaufort Gyre had accumulated 4600 km 3 of freshwater relative to the 2003–2006 mean. Doming of Arctic DOT in the Beaufort Sea is revealed by Empirical Orthogonal Function analysis to be concurrent with regional reductions in the Siberian Arctic. We estimate that the Siberian shelf seas lost ∼180 km 3 of freshwater between 2003 and 2014, associated with an increase in annual mean salinity of 0.15 psu yr −1 . Finally, ocean storage flux estimates from altimetry agree well with high‐resolution model results, demonstrating the potential for altimetry to elucidate the Arctic hydrological cycle. Key Points: SSH is estimated in the ice‐covered and ice‐free Arctic with bespoke radar altimeter data processing Arctic SSH is dominated by seasonal steric variation in response to summertime freshwater input Nonseasonal SSH variability dominated by bulging in the Beaufort Sea due to freshwater accumulation